Predisposition Factors in Exclusive Breastfeeding in Infants (Literature Review) - Subagyo; Suparji; Nana Usnawati; Vilia Tri Erlina (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. Nutritional intake inthe first thousand days of a child’s life up to 2 yesars old is very important forgrowth and development. The low number of exclusive breasfeeding is still to be concern of the Indonesiangovernmnet .Based on data from Magetan District Health Office in 2019, the coverage of exclusivebreastfeeding in the Poncol Puskesmas was 48,4 %. The purpose of this systematic literature review isto systematically review some of the results of recent research on the drivers that influence the success ofexclusive breastfeeding, namely the factors of knowledge, education, employment, and attitude.The typeof research used is systematic literature review (SLR) using the Preffered Reporting Items for SystematicReview and Meta Analysis (PRISMA) approach. The database used are DOAJ and SINTA (Garuda), the last5 years publication limits, analytical research, cross sectional research designs, full text articles, researchareas are Indonesia. From the research results found 546 journals and after screening obtained 9 relevantjournals. Regarding education, 3 out of 4 journals stated that there was a relationship between educationand exclusive breastfeeding. On the employment factor, 4 out 5 journals stated that there was a relationshipbetween wprk and exclusive breastfeeding. In the knowledge factor, all of journals stated that there was arelationship between knowledge and eclusive breastfeeding. While in the attitude factor, 3 out of 4 journalsstated that there was a relatioship between attitude and exclusive breastfeeding.The majority, of journal statethat there is relationship between education, knowledge, employment, and attitude of mother’s breatfeeding.It is hoped that the results of this review will be able to bring change to readers, especially health workerswho have a very important role in providing education and promotion regarding exclusive breastfeeding.